The decrease in phase angle measured by bioelectrical impedance analysis reflects the increased locomotive syndrome risk in community-dwelling people: The Yakumo study. Issue 3 (4th May 2019) - Tanaka, Satoshi; Ando, Kei; Kobayashi, Kazuyoshi; Hida, Tetsuro; Seki, Taisuke; Hamada, Takashi; Ito, Kenyu; Tsushima, Mikito; Morozumi, Masayoshi; Machino, Masaaki; Ota, Kyotaro; Ishiguro, Naoki; et al.
Abstract: Objectives: The locomotive syndrome (LS) risk test has recently been advocated for the evaluation of physical ability. Phase angle measurement by bioelectrical impedance analysis (BIA) is an indicator of cellular health and muscle mass. We aimed to investigate how muscle mass and phase angle are related to LS risk stage. Methods: A prospective cohort study was conducted in 311 patients who were undergoing a health checkup. All participants performed the two-step test, stand-up test, and 25-question geriatric locomotive function scale components of the LS risk test. Muscle mass and phase angle were measured using BIA. A comparison study was conducted among the three LS risk stages. Results: In the trend test, phase angle decreased significantly as the LS risk stage progressed, whereas muscle mass did not show a significant difference. After adjusting for age and sex, phase angle showed a significant difference among all LS risk stages. Muscle mass did not show a significant difference between no risk and stage 1. Conclusion: Compared to muscle mass, phase angle more strongly reflects LS risk and becomes significantly reduced at later LS risk stages. Phase angle can be a useful screening tool for LS risk.